UJI DAYA HAMBAT ASAP CAIR TEMPURUNG KELAPA (Cocos nucifera L.) TERHADAP PERTUMBUHAN Escherichia coli SECARA In Vitro - Lumban Tobing, Rachel Daniella Dinda Maria; Defiani, Made Ria; Susun Parwanayoni, Ni Made (SIMBIOSIS, 2021)
Meat contaminated with bacteria has the potential to cause dangerous diseases when consumed by humans. One of the germs, especially bacteria that contaminate raw meat or meat with an incomplete maturation process is Escherichia coli. Therefore, E. coli needs to be minimized by inhibiting its growth. One natural way to inhibit the growth of E. coli is to test for antibacterials using liquid smoke. Liquid smoke can be obtained through the pyrolysis process from various biomass containing cellulose, hemicellulose, and lignin such as coconut shell (Cocos nucifera L.). Liquid smoke contains phenolic and acid compounds which are antimicrobial and antioxidant. This research uses the diffusion well method. Data analysis used Completely Randomized Design (CRD) with variance test (ANOVA). If the data had a significant difference at the 5% test level (P?5), the Duncan test was continued. Coconut shell liquid smoke is able to inhibit the growth of E. coli which is indicated by the formation of an inhibition zone. The concentration of coconut shell liquid smoke which effectively inhibited the growth of E. coli was a concentration of 50% with an inhibition zone diameter of 16.66 mm and MIC at a concentration of 10% with an inhibition zone diameter of 9.33 mm. Phytochemical test results of coconut shell liquid smoke contain positive phenolic compounds, flavonoids, triterpenoids, and saponins as well as phenol content of 2.403% and saponin content of 5.50%.